Method for producing laminate of iron-based amorphous alloy
By stacking and heat-treating the iron-based amorphous alloy thin strip, a laminated body with suitable thickness and good soft magnetic characteristics is formed, which solves the problem of increasing the thickness of the iron-based amorphous alloy thin strip in the prior art, and realizes the manufacturing of high-efficiency motor iron core materials.
Patent Information
- Application Number
- CN202380055861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-07-04
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to effectively increase the thickness of the iron-based amorphous alloy thin strip, which makes it difficult to meet the thickness and performance requirements of the silicon steel plate when manufacturing the laminated iron core.
By stacking a plurality of thin strips of iron-based amorphous alloys and heat-treated, applying a thermosetting resin, and hot-pressing, forming a laminated body, and making an iron core material with suitable thickness and good soft magnetic properties by punching.
It is realized that the punching process can be easily performed while ensuring good soft magnetic characteristics, and is suitable for manufacturing efficient EV driving BLDC motor core materials.
Smart Images

Figure CN119604954A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a laminated body of an iron-based amorphous alloy, and more particularly, to a method for producing a laminated body of an iron-based amorphous alloy that can be suitably used for a laminated core of a motor, a generator, or the like. Background Art
[0002] In recent years, iron-based amorphous alloy materials with iron (Fe), boron (B), and silicon (Si) as main raw materials have become widely known for various passive components or transformer applications such as inductors and reactors used as electronic parts. Fe-SiB-based rapidly solidified alloy thin strips with a thickness of about 17μm to 22μm made by melt rapid solidification using such soft magnetic materials are used as winding cores for large transformers or rectifier inductors for power supply purposes, etc., and the demand is increasing year by year as a substitute for conventional silicon steel sheets (Fe-Si).
[0003] In addition, iron-based amorphous alloys have lower iron loss than silicon steel sheets, so they are used in the rotor core and stator core of BLDC (brushless DC) motors to improve motor efficiency. In particular, when applied to high-speed rotating BLDC motors exceeding 10,000 rpm, it is confirmed that the operating range of soft magnetic materials becomes a high-frequency band above 1 kHz, and the efficiency becomes more significant in motors of several hundred W. Therefore, it can be expected to be used in compressors for air-conditioning purposes, white appliances such as rechargeable vacuum cleaners, or auxiliary motors for electrical equipment purposes.
[0004] For EV drive motors, which are more efficient than white appliance motors, the market is also shifting to high-speed rotary BLDC motors with a rotation speed of more than 10,000 rpm (for example, around 20,000 rpm) due to market demands for miniaturization, high torque, and high efficiency. Therefore, iron-based silicon-boron amorphous alloys have been studied as soft magnetic materials with an operating range of 1 to 2 kHz when used as motor cores.
[0005] Compared with silicon steel sheets, iron-based silicon-boron amorphous alloys can reduce iron loss to about 1 / 10, have high magnetic permeability, and have a certain degree of high Bs (saturation magnetic flux density). Therefore, they have attracted attention in recent years as a new generation of high-performance soft magnetic materials. However, the thickness of iron-based silicon-boron amorphous alloys is usually around 17 to 25 μm, which is very thin compared to silicon steel sheets with a thickness of about 250 to 350 μm. Therefore, it is difficult to perform punching processing for manufacturing laminated cores, etc. Therefore, it has become a technical problem to increase the size of the manufactured iron-based silicon-boron amorphous alloy while maintaining its good properties.
[0006] For example, Non-Patent Document 1 discloses that a thin strip of an iron-based amorphous alloy having a thickness of 50 μm or more is obtained by reducing the rapid solidification rate by adding phosphorus (P). However, phosphorus-added alloys not only reduce Bs due to the addition of phosphorus, but also volatilize the phosphorus component during alloy melting, causing significant contamination inside and outside the melt rapid cooling device, and furthermore, there is a risk of flammability, so there are few examples of their application in the industrial field so far.
[0007] Patent Documents 1-3 disclose a method for producing an amorphous alloy strip having a thickness (e.g., about 50 μm) that can be punched by discharging alloy melt from multiple slit nozzles onto a rotating cooling roller using a multiple slit method. However, even with this technology, there is a limit to the increase in thickness, making it difficult to use as a soft magnetic material for laminated cores that replace silicon steel sheets.
[0008] Patent Document 4 discloses a method for manufacturing a metal strip using a multi-hole nozzle to suppress the uneven thickness of the metal strip when manufacturing a wide quenched thin strip. The invention of Patent Document 4 has a characteristic shape of the nozzle opening, but there is a problem that the nozzle processing fee is high due to the difficulty in processing, and it is difficult to use it at the mass production level.
[0009] Patent Document 5 discloses a method for producing an iron-based silicon-boron amorphous alloy using a liquid discharge nozzle having staggered multi-holes to achieve thickening of the plate. However, when compared with silicon steel plates, there is still room for improvement in ensuring sufficient thickness.
[0010] As described above, it is currently difficult to increase the thickness of an amorphous alloy ribbon itself, and therefore Patent Document 6 discloses a method for manufacturing a laminated body having a thicker layer by laminating a plurality of soft magnetic alloy ribbons.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Laid-Open No. 5-329587
[0014] Patent Document 2: Japanese Patent Application Laid-Open No. 7-113151
[0015] Patent Document 3: Japanese Patent Application Laid-Open No. 8-124731
[0016] Patent Document 4: Japanese Patent Application Laid-Open No. 63-220950
[0017] Patent Document 5: Japanese Patent Application Publication No. 2018-153828
[0018] Patent Document 6: Japanese Patent Application Publication No. 2021-154732
[0019] Non-patent literature
[0020] Non-Patent Literature 1: Creation of a new bulk metallic glass / amorphous thick plate with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Chuntao Chang Summary of the invention
[0021] Technical problem to be solved by the invention
[0022] In the method for manufacturing a laminate of soft magnetic alloy thin strips disclosed in Patent Document 6, a thermosetting resin is applied to at least one of a plurality of soft magnetic alloy thin strips, and after laminating them, they are heated at a predetermined temperature and bonded to form a laminate, which is then wound into a coil shape. When a laminate obtained by this manufacturing method is used to manufacture a laminated iron core, the laminate is unwound from a wound state, a plurality of core sheets are punched out by punching, and the core sheets are then riveted and stacked.
[0023] In the method for manufacturing a laminate of soft magnetic alloy ribbons disclosed in Patent Document 6, the soft magnetic alloy ribbons may be amorphous alloy ribbons, or may be nanocrystalline alloy ribbons obtained by heat treating amorphous alloy ribbons. However, since the heat treatment conditions have a significant impact on the magnetic permeability of the soft magnetic alloy ribbons, there is room for research in ensuring good soft magnetic properties.
[0024] In addition, in the method for manufacturing a laminate of soft magnetic alloy thin strips disclosed in Patent Document 6, by winding the manufactured laminate into a coil shape, positional deviation is likely to occur between the plurality of soft magnetic alloy thin strips constituting the laminate, and there is a risk that a portion of the soft magnetic alloy thin strip will peel off. Therefore, the characteristics of the laminated core manufactured by unfolding the laminate are likely to deviate, and there is a risk that sufficient quality cannot be obtained.
[0025] In order to achieve high efficiency of high-speed rotary motors such as the next-generation EV drive motors that are driven at high speeds of 10,000 rpm to 20,000 rpm, low iron loss and high magnetic permeability are required relative to the silicon steel sheets used as existing core materials. Specifically, soft magnetic properties of Bs ≥ 1.5 T, magnetic permeability ≥ 3000, and iron loss ≤ 30 W / kg (Bm: 1.0 T, 1 kHz) are required. Furthermore, the automotive industry is eager to use iron-based amorphous alloys as core materials for BLDC motors used for EV drive. While ensuring good soft magnetic properties, the iron-based amorphous alloys have a thickness that allows the manufacture of laminated cores by punching at the same efficiency as silicon steel sheets.
[0026] Therefore, an object of the present invention is to provide a method for producing a laminated body of an Fe-based amorphous alloy, which can easily perform a punching process while ensuring good soft magnetic properties.
[0027] Solutions for solving the above technical problems
[0028] The object of the present invention is to realize a method for manufacturing a laminated body of an iron-based amorphous alloy thin strip, which is a method for manufacturing a laminated body by stacking a plurality of iron-based amorphous alloy thin strips, wherein the iron-based amorphous alloy thin strip has the following composition: 100-x-y-z Si x (B 1-m C m ) y P z (T is at least one element selected from the group consisting of Fe, Co and Ni, and is a transition metal element that must include Fe), the composition ratios x, y, z and m respectively satisfy 2.5≤x≤7.0atomic%, 13.0≤y≤16.0atomic%, 0.0≤z≤2.0atomic%, 0.0≤m≤0.3, and the thickness of the iron-based amorphous alloy strip composed of this composition is not less than 30μm and not more than 60μm. The manufacturing method of the stack of the iron-based amorphous alloy strips comprises: a pretreatment step of heat-treating a plurality of the iron-based amorphous alloy strips at a temperature not less than 200°C and not more than the crystallization temperature; a coating step of coating at least any one of the plurality of the heat-treated iron-based amorphous alloy strips with a thermosetting resin to form an adhesive layer; and a hot pressing step of forming a stack by hot pressing the plurality of the iron-based amorphous alloy strips via the adhesive layer.
[0029] Preferably, in the pretreatment step, the heat treatment is performed for a heat treatment time of 0.01 seconds to 2 hours.
[0030] Preferably, in the pretreatment step, the heat treatment is performed while the plurality of the iron-based amorphous alloy thin strips are overlapped and tightly bonded; preferably, in the coating step, the plurality of overlapping iron-based amorphous alloy thin strips are separated to form the bonding layer.
[0031] Preferably, there is further provided a punching step of conveying the stacked body of the iron-based amorphous alloy thin strips obtained in the hot compression bonding step to a punching press without winding it, and punching it into a predetermined shape by the punching press to form a punched sheet.
[0032] Preferably, in the thermocompression bonding step, the thermocompression bonding is performed at a temperature of 120° C. to less than 400° C. for 1 second to less than 60 seconds, and the thickness of the stack of the Fe-based amorphous alloy thin strips is 80 μm to 400 μm.
[0033] In the thermal compression bonding step, the pressure during thermal compression bonding is 30 N to 1 kN per square cm, preferably 100 N to 700 N, and more preferably 100 N to less than 400 N, at a temperature of 120° C. to 400° C. for 1 second to 60 seconds. Thus, when punching the laminated body made of the iron-based amorphous alloy thin strip, good adhesion between the laminated bodies can be easily ensured without peeling.
[0034] Preferably, the iron-based amorphous alloy ribbon having undergone the pretreatment step has a Bs of 1.5 T or more, a magnetic permeability of 3000 or more, and an iron loss of 30 W / kg or less at Bm=1.0 T and a frequency of 1 kHz.
[0035] Effects of the Invention
[0036] According to the method for producing a laminate of an iron-based amorphous alloy of the present invention, punching can be easily performed while ensuring good soft magnetic properties, and thus, for example, it can be suitably used to produce a core material for a BLDC motor for driving an EV. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a flowchart for explaining a method for producing a laminate of an iron-based amorphous alloy according to one embodiment of the present invention.
[0038] Figure 2 It is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to one embodiment of the present invention.
[0039] Figure 3 It is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to another embodiment of the present invention.
[0040] Figure 4 It is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to still another embodiment of the present invention. DETAILED DESCRIPTION
[0041] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Figure 1 FIG. 1 is a flowchart for explaining a method for manufacturing a laminate of an iron-based amorphous alloy according to an embodiment of the present invention. Figure 1As shown in the figure, the method for manufacturing a laminate of an iron-based amorphous alloy according to the present embodiment includes: a pretreatment step S1 of heat-treating a plurality of iron-based amorphous alloy thin strips; a coating step S2 of forming an adhesive layer on the heat-treated iron-based amorphous alloy thin strips; a hot press bonding step S3 of laminating and hot press bonding a plurality of iron-based amorphous alloy thin strips via the adhesive layer; and a blanking step S4 of blanking the laminate obtained by hot press bonding into a specified shape to form a blanked sheet. Hereinafter, with reference to Figure 2 the schematic process chart shown in the figure, each of the steps S1 to S4 will be described.
[0042] <S1: Pretreatment Step>
[0043] As disclosed in the above-mentioned Patent Document 5, the iron-based amorphous alloy thin strip is obtained by forming an alloy melt into a thin strip shape by a single-roll melt rapid solidification method in which the alloy melt is rapidly cooled and solidified by contacting a cooling roll, and the iron-based amorphous alloy thin strip thus formed can be preferably used. As Figure 2 shown in the figure, in the pretreatment step S1, a plurality of (three in the present embodiment) iron-based amorphous alloy thin strips 1 are respectively unwound from the state of being wound around the delivery roll 10 and conveyed to the pretreatment constant temperature bath 20, and heat treatment is performed in the pretreatment constant temperature bath 20.
[0044] To obtain good soft magnetic properties, the following iron-based amorphous alloy thin strip 1 is used: the composition formula is expressed as T 100-x-y-z Si x (B 1-m C m ) y P z (T is at least one element selected from the group consisting of Fe, Co, and Ni, and is a transition metal element that must contain Fe), and the composition ratios x, y, z, and m respectively satisfy 2.5 ≤ x ≤ 7.0 atomic %, 13.0 ≤ y ≤ 16.0 atomic %, 0.0 ≤ z ≤ 2.0 atomic %, and 0.0 ≤ m ≤ 0.3.
[0045] If the thickness of the iron-based amorphous alloy thin strip 1 is too thin, since the number of laminated sheets for forming the laminate increases, there is a risk of increasing the manufacturing cost. On the other hand, if it is too thick, the manufacturing becomes difficult. Therefore, the thickness of the iron-based amorphous alloy thin strip 1 is 30 μm or more and 60 μm or less. The width of the iron-based amorphous alloy thin strip 1 is not particularly limited, but in the case of assuming use as a motor core, for example, it is 10 to 200 mm.
[0046] If the heat treatment temperature in the pretreatment process S1 is increased to the temperature of clusters that are precursors of crystal phases in the iron-based amorphous alloy or the temperature of nanoscale crystals crystallized after cluster crystallization as in the past, the magnetic permeability decreases and it is difficult to obtain the desired soft magnetic properties. Therefore, the heat treatment temperature is set below the crystallization temperature of the iron-based amorphous alloy. The crystallization temperature refers to the temperature (inflection point) at which heat generation starts due to the crystallization of the iron-based amorphous alloy and can be measured by a differential scanning calorimeter (DSC), a differential thermal analyzer (DTA), etc. The specific crystallization temperature varies depending on the alloy composition, etc., and is, for example, 350 to 500 °C.
[0047] On the other hand, if the heat treatment temperature in the pretreatment process S1 is too low, the improvement of the soft magnetic properties of the iron-based amorphous alloy strip 1 will not occur. Therefore, the heat treatment temperature is set at 200 °C or higher. The heat treatment temperature in the pretreatment process S1 is preferably 240 to 280 °C. In this way, by setting the heat treatment temperature of the pretreatment process S1 lower than in the past, the iron-based amorphous alloy strip 1 can be cooled in a short time, and the coating process S2 of the next process can be started earlier, so that the conveying distance of the iron-based amorphous alloy strip 1 before the next process can be shortened or the conveying speed can be increased, and the manufacturing efficiency can be improved. When the thickness of the iron-based amorphous alloy strip 1 is relatively large (30 μm or more and 60 μm or less), the heat treatment temperature in the pretreatment process S1 is crucial for obtaining good soft magnetic properties.
[0048] The heat treatment in the pretreatment process S1 can be carried out instantaneously. By performing the heat treatment time in a short time, miniaturization of the pretreatment constant temperature bath 20 can be achieved. Specifically, the heat treatment time is preferably 0.01 seconds or more. There is no particular limitation on the upper limit of the heat treatment time, but if the time is too long, the manufacturing efficiency will be significantly reduced. Therefore, it is, for example, 2 hours or less.
[0049] The pretreatment process S1 is preferably carried out in a state where a plurality of iron-based amorphous alloy strips 1 are overlapped and closely adhered to each other by the crimping rollers 21 and 22. Thus, the heat treatment of each iron-based amorphous alloy strip 1 can be carried out efficiently while saving space.
[0050] The iron-based amorphous alloy strip 2 heat-treated by the pretreatment process S1 can easily achieve the following soft magnetic properties of a laminated core applicable to a small and high-efficiency BLDC motor for EV drive: Bs is 1.4 T or more, the magnetic permeability is 3000 or more, and the iron loss is 30 W / kg or less at Bm = 1.0 T and a frequency of 1 kHz.
[0051] <S2: Coating process>
[0052] The heat-treated iron-based amorphous alloy ribbons 2 are discharged from the pretreatment constant temperature bath 20 in a state where multiple ribbons are overlapped. In the coating step S2, after separating each iron-based amorphous alloy ribbon 2, one or both sides of the bonding surface when stacking multiple iron-based amorphous alloy ribbons 2 again are coated with an adhesive using a coating device 31. The coating device 31 in the present embodiment is a spray type, but a roll coater, a curtain coater, a dispensing machine, etc. can also be used. The adhesive is composed of a thermosetting resin. In the present embodiment, an epoxy resin is used, but a polyester resin, a polyimide resin, a polyurethane resin, etc. can also be used. Coating the adhesive on the heat-treated iron-based amorphous alloy ribbons 2 is preferably performed uniformly over the entire bonding surface. The film thickness of the adhesive is, for example, 0.1 μm to 20 μm.
[0053] During the process of transporting the adhesive coated on the heat-treated iron-based amorphous alloy ribbons 2 to the hot press bonding constant temperature bath 40 for the next step of the hot press bonding step S3, drying is performed by a drying device 32 such as a heater. Thereby, a bonding layer 3 is formed on the bonding surface of the iron-based amorphous alloy ribbons 2.
[0054] <S3: Hot Press Bonding Step>
[0055] In the hot press bonding step S3, each heat-treated iron-based amorphous alloy ribbon 2 is bonded via the bonding layer 3 by the press rollers 41 and 42, and hot press bonding is performed in the hot press bonding constant temperature bath 40, thereby forming a laminate 4 of the iron-based amorphous alloy ribbons 2. If the heating temperature of the laminate 4 in the hot press bonding step S3 is too low, sufficient adhesive force cannot be exhibited due to insufficient curing of the bonding layer 3. On the other hand, if the heating temperature is too high, the bonding strength between the iron-based amorphous alloy ribbons 2 may decrease after the bonding layer 3 is cured, and thus it is likely to cause delamination between the iron-based amorphous alloy ribbons 2 constituting the laminate 4 in the next punching step S4. Therefore, in order to ensure good adhesion between the iron-based amorphous alloy ribbons 2, it is preferable to set the temperature in the hot press bonding constant temperature bath 40 to 120°C or higher and lower than 400°C, more preferably 150°C or higher and lower than 350°C. The heating time of the laminate 4 in the hot press bonding constant temperature bath 40 based on holding can be 1 second or more and less than 2 hours, preferably 5 seconds or more and less than 1 hour, and further preferably 7 seconds or more and less than 30 minutes.
[0056] The hot pressing pressure in the hot pressing process S3 can be 30 N or more and 1 kN or less per 1 square cm. If the hot pressing pressure is lower than 30 N, the tightness between the mutually adhered iron-based amorphous alloy thin strips 2 cannot be sufficiently ensured. On the other hand, if the hot pressing pressure exceeds 1 kN, strain is generated inside the iron-based amorphous alloy thin strip 2, reducing the soft magnetic properties. Considering the balance between the tightness strength and the soft magnetic properties, the hot pressing pressure is preferably 100 N or more and 700 N or less per 1 square cm, and more preferably 100 N or more and less than 400 N.
[0057] The thickness of the laminate 4 of the iron-based amorphous alloy thin strips 2 formed by the hot pressing process S3 is preferably a thickness that enables blanking processing at the same efficiency level as that of conventional silicon steel sheets. Specifically, the thickness of the laminate 4 is preferably 80 μm or more and 400 μm or less, and more preferably 100 μm or more and 300 μm or less. The thickness of each iron-based amorphous alloy thin strip 2 and the number of laminated sheets can be appropriately set in consideration of the required thickness of the laminate 4.
[0058] <S4: Blanking Process>
[0059] The laminate 4 of the iron-based amorphous alloy thin strips 2 formed by the hot pressing process S3 is conveyed to a blanking press 50, and the blanking process S4 is performed by the blanking press 50. In the blanking process S4, the laminate 4 is clamped by the upper die and the lower die of the blanking press 50 and blanked into a specified shape, and blanked sheets 5 such as stator core plates are continuously formed. A stretching roller 51 is provided on the downstream side in the conveying direction of the blanking press 50, and by driving the stretching roller 51, a tensile force in the direction of arrow A acts on the laminate 4, and the laminate 4 is blanked in this state.
[0060] Thus, by directly conveying the laminate 4 of the iron-based amorphous alloy thin strips 2 obtained by the hot pressing process S3 to the blanking press 50 without winding for the blanking process S4, since there is no risk of problems such as position deviation or peeling of the iron-based amorphous alloy thin strips 2 caused by winding the laminate 4, high-quality blanked sheets 5 can be efficiently manufactured. In addition, regarding the laminate 4 after blanking the blanked sheets 5, it can be melted and reused after being wound or cut to an appropriate length.
[0061] According to the manufacturing method of the laminate of the iron-based amorphous alloy thin strip of the present embodiment, a laminate 4 of the iron-based amorphous alloy 2 can be obtained that can be easily blanked while ensuring good soft magnetic properties.
[0062] The above has detailed one embodiment of the present invention, but the specific embodiment of the present invention is not limited to the above embodiment. For example, in the pre-treatment process S1 of the present embodiment, heat treatment is performed in a state where a plurality of iron-based amorphous alloy thin strips 1 are overlapped and tightly adhered, but it can also be as Figure 3As shown, the Fe-based amorphous alloy thin strips 1 unrolled from the respective delivery rollers 10 are respectively transported to the pre-treatment constant temperature bath 20 for heat treatment.
[0063] In addition, in the present embodiment, the pre-treatment step S1, the coating step S2, the thermal compression bonding step S3 and the punching step S4 are performed as a series of steps, but each step may be divided. Figure 4 As shown in (a), the iron-based amorphous alloy thin strip 1 unwound from the delivery roller 10 is transported to the pretreatment constant temperature bath 20 for pretreatment step S1, and the heat-treated iron-based amorphous alloy thin strip 2 is wound onto the first winding roller 11. Figure 4 As shown in (b), the two sides of the iron-based amorphous alloy thin strip 2 unwound from the first winding roll 11 are subjected to a coating step S2 of forming an adhesive layer 3 by a coating device 31 and a drying device 32, and then the thin strip is wound onto the second winding roll 11. Thus, after a plurality of second winding rolls 11 wound with the iron-based amorphous alloy thin strip 2 are formed, as shown in FIG. Figure 4 As shown in (c), the iron-based amorphous alloy thin strip 2 is unwound from these second winding rollers 11 and overlapped by the pressure-bonding rollers 41 and 42, and then transported to the thermostatic tank 40 for hot pressing to perform the hot pressing step S3. Next, the laminated body 4 formed by the hot pressing step S3 is transported to the punching press 50 for the punching step S4, thereby forming the punched sheet 5. Thus, by appropriately dividing each step S1 to S4, the free space on site can be effectively utilized to manufacture the laminated body 4 and the punched sheet 5.
[0064] Hereinafter, the present invention will be described in further detail based on examples and comparative examples of the present invention. However, the present invention is not limited to the following examples.
[0065] (Example)
[0066] 200 kg of raw materials mixed with B, C, Si, P and Fe with a purity of 99.5% or more were inserted into an alumina crucible in order to form the alloy compositions shown in Examples 1 to 6 of Table 1 below, and melted by high-frequency induction heating to form an alloy melt. 50 kg of the alloy melt was injected into an alumina liquid storage container with an inner diameter of 200 mm × a height of 400 mm, and the liquid storage container had a BN liquid discharge nozzle with a slit of 0.5 mm wide × 40 mm long at the bottom. A copper alloy quenching roller with a diameter of 1000 mm and a width of 200 mm was arranged at a distance of 0.4 mm directly below the liquid discharge nozzle, and the quenching roller was rotated at a surface speed of 25 m / s, and the alloy melt was discharged from the liquid discharge nozzle to the outer peripheral surface to ultra-rapidly cool the melt, thereby producing an iron-based amorphous alloy thin strip having an amorphous alloy structure of 90% or more by volume. The thickness of the produced iron-based amorphous alloy thin strip is shown in Table 1. The injection pressure of the alloy melt discharged from the liquid discharge nozzle was 30 kPa, and the amount of cooling water supplied to the inner wall of the chill roll was 300 liters per minute.
[0067] The obtained Fe-based amorphous alloy thin strip was continuously conveyed in the atmosphere by a mesh belt furnace and subjected to heat treatment at a temperature below the crystallization temperature as a pretreatment. The heat treatment temperature and heat treatment time at this time are shown in Table 1.
[0068] Next, multiple pieces of iron-based amorphous alloy thin strips that have been heat-treated as a pretreatment are overlapped to make a laminate of iron-based amorphous alloy thin strips. When making the laminate, a thermosetting resin is evenly applied to the joint surface of the iron-based amorphous alloy thin strips so that the thickness becomes less than several μm, and then the strips are continuously inserted into a tunnel furnace while being sandwiched by a pressure roller, and a hot pressing treatment is performed in the atmosphere. The number of stacked sheets, hot pressing temperature, hot pressing time, hot pressing force, and the thickness of the obtained laminate are shown in Table 2.
[0069] After evaluating the soft magnetic properties (saturation magnetic flux density Bs, relative magnetic permeability μr and iron loss) of the obtained laminate, a punching test was performed by a punching press. The adhesion of each iron-based amorphous alloy thin strip after punching was evaluated by dividing it into the following three cases: ○ when no peeling of the thin strips was observed, △ when partial peeling was observed, and × when the strips were completely peeled. The evaluation results are shown in Table 3 below.
[0070] (Comparative Example)
[0071] Alloy melts were formed to have the alloy compositions shown in Comparative Examples 7 to 11 in Table 1 below, and Fe-based amorphous alloy ribbons were produced from the alloy melts. The production conditions of Comparative Examples 7 to 10 were the same as those of Examples 1 to 6, except that the size of the slit of the liquid discharge nozzle was set to 0.3 mm in width × 40 mm in length. On the other hand, the production conditions of Comparative Example 11 were the same as those of Examples 1 to 6, including the size of the slit of the liquid discharge nozzle.
[0072] Afterwards, the iron-based amorphous alloy strips of Comparative Examples 7, 10 and 11 were subjected to heat treatment as a pretreatment using a mesh belt furnace in the same manner as in Examples 1-6. The heat treatment temperature and heat treatment time at this time are shown in Table 1. The heat treatment temperature of Comparative Example 11 is a temperature higher than the crystallization temperature of the iron-based amorphous alloy strip having an amorphous structure. On the other hand, the iron-based amorphous alloy strips of Comparative Examples 8 and 9 were not subjected to heat treatment as a pretreatment.
[0073] Next, similarly to Example 1-6, a laminate of an iron-based amorphous alloy thin strip was prepared under the conditions shown in Table 2, and the soft magnetic properties (saturation magnetic flux density Bs, relative magnetic permeability μr, and iron loss) of the obtained laminate were evaluated. Then, a blanking test was performed by a blanking press to evaluate the adhesion of each iron-based amorphous alloy thin strip after blanking. The evaluation results are shown in Table 3 below.
[0074] [Table 1]
[0075]
[0076] [Table 2]
[0077]
[0078] [Table 3]
[0079]
[0080] Description of Reference Numerals
[0081] 1. Iron-based amorphous alloy strip
[0082] 2 Iron-based amorphous alloy strip after heat treatment
[0083] 3 Adhesive layer
[0084] 4-layer stack
[0085] 5 Punching pieces
[0086] 10 Delivery roller
[0087] 20 Constant temperature bath for pre-treatment
[0088] 21, 22 crimping roller
[0089] 31 coating device
[0090] 32 Drying device
[0091] 40 Constant temperature bath for thermal compression bonding
[0092] 41, 42 crimping roller
[0093] 50 Blanking Press
[0094] S1 Pre-treatment process
[0095] S2 coating process
[0096] S3 Thermocompression Process
[0097] S4 punching process.
Claims
1. A method for manufacturing a laminate of an iron-based amorphous alloy thin strip, which is a method for manufacturing a laminate by laminating a plurality of iron-based amorphous alloy thin strips, characterized in that: The iron-based amorphous alloy strip has the following composition: 100-x-y-z Si x (B 1-m C m ) y P z The composition ratios x, y, z and m satisfy 2.5≤x≤7.0 atomic %, 13.0≤y≤16.0 atomic %, 0.0≤z≤2.0 atomic %, and 0.0≤m≤0.3, respectively; the thickness of the Fe-based amorphous alloy strip composed of the composition is 30 μm to 60 μm, wherein T is at least one element selected from the group consisting of Fe, Co and Ni, and is a transition metal element that must contain Fe. The method for manufacturing a laminate of the iron-based amorphous alloy thin strips comprises: A pre-treatment step of heat treating the plurality of the iron-based amorphous alloy thin strips at a temperature above 200° C. and below a crystallization temperature; A coating step of coating at least any one of the plurality of heat-treated iron-based amorphous alloy thin strips with a thermosetting resin to form an adhesive layer; The thermal compression bonding step forms a laminated body by thermally compressing the plurality of the iron-based amorphous alloy thin strips via the adhesive layer.
2. The method for manufacturing a laminate of an iron-based amorphous alloy thin strip according to claim 1, characterized in that: In the pretreatment step, the heat treatment is performed for a heat treatment time of 0.01 seconds to 2 hours.
3. The method for manufacturing a laminate of an iron-based amorphous alloy thin strip according to claim 1, characterized in that: In the pre-treatment step, a plurality of the iron-based amorphous alloy thin strips are overlapped and closely bonded to perform heat treatment. In the coating step, the plurality of superimposed Fe-based amorphous alloy thin strips are separated to form the adhesive layer.
4. The method for manufacturing a laminate of an iron-based amorphous alloy thin strip according to claim 1, characterized in that: The method further comprises a punching step of conveying the stacked body of the iron-based amorphous alloy thin strips obtained in the hot compression bonding step to a punching press without winding it, and punching it into a predetermined shape by the punching press to form a punched sheet.
5. The method for manufacturing a laminate of an iron-based amorphous alloy thin strip according to claim 1, characterized in that: In the thermocompression bonding step, the thermocompression bonding is performed at a temperature of 120° C. or higher and lower than 400° C. for 1 second or higher and lower than 2 hours, and the thickness of the stack of the Fe-based amorphous alloy thin strips is 80 μm or higher and 400 μm or lower.
6. The method for manufacturing a laminate of an iron-based amorphous alloy thin strip according to claim 1, characterized in that: The pressing force in the thermal pressing step is not less than 30 N and not more than 1 kN per 1 square cm.
7. The method for manufacturing a laminate of Fe-based amorphous alloy thin strips according to claim 1, characterized in that: The iron-based amorphous alloy thin strip that has undergone the pretreatment step has a Bs of 1.4 T or more, a magnetic permeability of 3000 or more, and an iron loss of 30 W / kg or less at Bm=1.0 T and a frequency of 1 kHz.
Citation Information
Patent Citations
Production of metal strip and nozzle for production
JP1988220950A
Production of thin strip of amorphous alloy having large thickness
JP1993329587A
Ferrous amorphous alloy
JP1995113151A
Multilayered magnetic alloy thin strap
JP1996124731A
METHOD FOR PRODUCING Fe-Si-B BASED RAPID-SOLIDIFIED ALLOY THIN STRIP
JP2018153828A